(untitled) (Research, Society and Development, 2021)
The Hypertrophic Cardiomyopathy (HCM) is a cardiac disease from genetic bases and most common hereditary transmission, has been identified numerous mutations in the genes of the cardiac sarcomere. The major characteristic of the disease is left ventricular hypertrophy (LVH) of diferente morphologies, without other causes that explain the condition. Its clinical manifestations vary according to the mutations of each individual and/or family; the patient may present in the asymptomatic form, or evolve with outcomes such as arrhythmias, subvalvular aortic stenosis, heart failure and even sudden death. Thus, the objective of this work is to approach the main clinical manifestations of HCM. An Integrative Literature Review was carried out, searching the Scielo, LILACS, UpToDate and MEDLINE databases. Articles published from 2015 to 2021, in full and available electronically in English, Spanish or Portuguese, were included. Articles that were repeated themselves, made available only in summary or unrelated to the purpose of the study, were excluded. Has been found 17.796 publications summing all platforms, after using the inclusion and exclusion criteria and using the descriptors 3187 articles remained; then, after reading the titles and/or abstracts, 25 articles were selected and analyzed. Therefore, it was understood that HCM is a silent disease in many cases, making screening essential to detect the disease early and allow precocious medical intervention, improving the prognosis and quality of life of patients; in addition, there is great difficulty in determining the risk of developing clinical manifestations, such as sudden cardiac death (SCD).